Screening of Combinatorial Quality Markers for Natural Products by Metabolomics Coupled With Chemometrics. A Case Study on Pollen Typhae - Ding, Mingya; Jiang, Yan; Yu, Xiean; Zhang, Dong; Li, Jin; Wang, Hui; Shen, Jiayuan; Gao, Xiu-mei; Chang, Yan-xu (Frontiers in Pharmacology, 2018)
Natural products, especially for traditional Chinese medicines (TCMs), are of great importance to cure diseases. Yet it was hard to screen the influential quality markers for monitoring the quality. A simple and comprehensive strategy was developed and validated to screen for the combinatorial quality markers for precise quality evaluation and discrimination of natural products. In this study, Pollen Typhae (PT) and it's processed products carbonized PT were selected as the representative case. Firstly, metabolomics data of 49 batches crude PT and carbonized PT was obtained by ultra high-performance liquid chromatography coupled with quadrupole time-of-flight mass spectrometry (UHPLC-Q-TOF/MS). Then, metabolomics approaches were performed to screen for the potential markers that led to the quality difference. Finally, chemometric methods were used to validate the accuracy of combinatorial quality markers. Thus, 42 compounds were identified from PT, 5 markers (isorhamnetin-3-O-(2G-α-L-rhamnosyl)-rutinoside, isorhamnetin-3-O-neohesperid oside, astragalin, kaempferol and umbelliferone) were successfully screened, identified, quantified and regarded as combinatorial quality markers for precise quality evaluation of crude and carbonized PT. It was demonstrated that the established comprehensively strategy provide an efficient tool for precise quality evaluation of natural products from the whole.